PENINGKATAN KEMAMPUAN PENGGUNAAN TANDA BACA MELALUI MEDIA PAPAN DETEKTIF TANDA BACA PADA MURID KELAS III SD - Ihsan Intania; Lingga Nico Pradana; Sri Pudjiwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the suboptimal punctuation skills of third-grade students at SDN 05 Madiun Lor, primarily caused by conventional learning methods. The research aims to improve students' punctuation usage through the Punctuation Detective Board Media. This Classroom Action Research was conducted in two cycles, encompassing planning, acting, observing, and reflecting. The subjects were 29 third-grade students. Data were collected via tests, observations, and documentation, then analyzed using descriptive quantitative and qualitative techniques. The results indicate a significant improvement in students' punctuation abilities. The average score increased from 70.34 in the pretest to 88.62 in Cycle I, and further to 94.14 in Cycle II. Moreover, the learning completeness percentage rose from 27.59% initially to 93.10% in Cycle I, and reached 96.55% in Cycle II. Beyond academic outcomes, the media successfully enhanced student activity, participation, and enthusiasm during the learning process. It is concluded that the Punctuation Detective Board Media is highly effective in improving punctuation skills among third-grade elementary students.